Identifying the Dynamic Influence of Economic Policy Uncertainty on Enterprise Investment Using Functional Data Analysis. (17th March 2022) - Wang, Deqing; Liu, Tianqi; Li, Xuemei; Huang, Yi; Zhou, Yuanhang
Abstract : Economic policy uncertainty (EPU) is one of the important influencing factors for enterprise investment. By its nature, enterprise investment is dynamically affected by uncertainty. We examine the time-varying impact of EPU on the level of corporate investment by introducing functional data analysis (FDA). Based on smoothing the discrete data of 106 China Securities Index (CSI) 300 firms into the continuous curve, we examine the dynamic relationship between EPU on corporate investment level and investment efficiency. In addition, we explore the effect of EPU on the level of corporate investment and investment efficiency after grouping regressions in a functional model. The findings show the following: Firstly, there is a suppressive effect of rising EPU on the level of corporate investment. However, when the EPU is low, it has a significant promoting effect on the level of corporate investment and gradually decreases with the increase of uncertainty level. Secondly, elevated EPU has a promoting effect on the efficiency of corporate investment. The inhibitory effect on firm investment efficiency is observed at low EPU and changes to a promotional effect at high EPU. Thirdly, increasing EPU has a greater inhibitory role in the investment level of nonstate firms and a greater promotional role in the investment efficiency of state firms. We seek to expand the research on the impact of macrouncertainty on microfirm investment and introduce FDA to provide a meaningful reference to solve the current controversial issue.